Optimización del proceso productivo de la empresa INCUBANDINA S.A. mediante la aplicación de tiempos y movimientos. - Vilca Llano, Cristian Javier (2019)
This investigation project was designed to improve the times of production, so it is an activity that stablishes an standard time with an specific task, so that the company will be productive, according to the times and movements , then, it solves the problems according to the process of slaughtering, (return to stunning by no electric shock, section before table of eviscerate, cut of culera and stoppage for maintenance), So it is possible to determine a time of production which is about 8,7 hours and an efficiency about 69,2. It found bottlenecks in the productive process. The company INCUBANDINA S.A., is in inadequate conditions and to avoid the good development of employees in different areas (pre- chiller and chiller) it finds with time work and for this reason, we perform the study of times and movements which it goes an optimized production process, for obtaining a time about 5,79 with efficiency about 82,7 in this process.